Pornography consumption among medical students in Syria: Prevalence, patterns, and predictors - Ahmad Al-Bitar; Dana Al-Masalma; Mohammad Adi; Thayr Haydar (PLoS ONE, 2026)
Background Pornography consumption is a global phenomenon, yet empirical research from the Middle East, particularly Syria, is nonexistent. Medical students may be especially vulnerable due to high stress levels. This study aimed to investigate the prevalence, patterns, and self-perceived effects of pornography consumption among medical students in Syria, addressing a significant geographical and cultural gap in the literature. Materials and methods A cross-sectional study was conducted between August 1, 2024, and November 30, 2024, by researchers from Damascus University Faculty of Medicine, Damascus, Syrian Arab Republic. An anonymous online questionnaire adapted from a validated instrument was distributed to Syrian medical students through official university channels and social media platforms. The final sample included 960 participants. The survey collected data on sociodemographics, consumption patterns, self-perceived addiction, cessation attempts, and effects on mental health, academic performance, and sexual satisfaction. Data were analyzed using descriptive statistics, non-parametric tests, and binary logistic regression. Results Lifetime exposure to pornography was reported by 720 participants (74.9%), with a mean age of first exposure of 14.8 ± 3.2 years. Logistic regression revealed that high family income (AOR = 2.15, 95% CI [1.48–3.12]) and having a private room (AOR = 3.48, 95% CI [2.51–4.83]) were significant predictors of lifetime exposure (p < 0.001), while gender was not a significant factor (p = 0.442). Nearly half of the students (463 participants, 48.2%) were current users. Among users, 236 (51.0%) had attempted to quit, with 170 (72.2%) experiencing adverse effects including erotic dreams (53.5%), irritability (26.4%), and attention disturbance (26.0%). Self-perceived addiction was reported by 117 participants (12.2%) overall and 72 participants (15.5%) among current users, with early exposure (≤12 years) being the strongest predictor (males: OR = 7.25, 95% CI [4.16–12.63]; females: OR = 4.23, 95% CI [2.85–6.28]). Conclusion This first investigation of pornography consumption among Syrian medical students reveals high lifetime exposure beginning in early adolescence, associated primarily with socioeconomic factors rather than gender. Cessation attempts and withdrawal-like symptoms were common among current users. Self-perceived addiction was strongly predicted by early exposure, particularly among males. These findings highlight the need for culturally tailored, non-judgmental support services and longitudinal research using validated instruments.